Demineralization of Turkish Tosya lignite coal by boric acid leaching. Issue 18 (16th September 2016) - Hacifazlioglu, Hasan; Uckan, Dilara; Sahin, Musa
ABSTRACT: Boric acid is a weak inorganic acid type which is generally being used in glass, ceramics, detergents, agriculture, nuclear energy, and medicine fields, which has white crystal color and which can easily dissolve in water. Boric acid is being produced from colemanite which is a boron mineral having wide reserves in Turkey. In recent years, intense studies have been performed on the alternative usage areas of boric acid in Turkey. In this study, boric acid was used as a leaching reagent for the demineralization of coal with high ash content. For the accurate determination of the success of boric acid in dissolving mineral matter, first a series of leaching tests were performed with boric acid, and then studies for removing mineral matter with strong acids such ashydrofluoric acid ( HF), HCl, and H2 SO4 were performed.